Ownership Structure, Corporate Governance and Financial Performance: A Study of Public Listed Companies in Malaysia - Wong, Jyh Juan (2006)
This research study is aimed at the top 200 capitalized companies listed in Bursa Malaysia as of 31 December 2005. We analyzed these companies’ corporate governance disclosure and practices, financial performance and whether there are significant relationship between having good corporate governance and achieving better financial outcome. The uniqueness of this study from others is that we segregate the findings based on different ownership structures of these sample companies, for comparative purpose. Hence we would also be able to understand better the background and motivation of these different entities of family controlled companies (FCCs), government linked companies (GLCs) and multinational companies (MNCs) in their governance practice and financial performance. The most interesting findings from this research objective are: GLCs generally have better corporate governance, followed by MNCs and FCCs in terms of overall weighted scores of Corporate Governance Survey (CGSR) for year 2005. However, surprisingly MNCs have best basic compliance score as compared to other local entities. MNCs generally have better financial performances in terms of Earning per Share (EPS), Price-Earning Ratio (PER) and Return on Equity (ROE), followed by FCCs and GLCs. However out of the four financial performance measures used, GLCs generally have higher Net Profit after Tax (NPAT) comparatively. As for the relationship between corporate governance and financial performance: For total samples, NPAT has significant correlation with CGSR 2005 weighted average scores and international best practice of corporate governance, whilst EPS only correlates significantly with international best practice score. As for different ownership structures, MNCs show strong correlation between corporate governance (particularly international best practice) with EPS, NPAT and ROE respectively. GLCs and FCCs only correlates significantly in terms of NPAT and international best practice scores, and this raises the question of benefit in having good corporate governance for these local entities.